Lurker dalam Konteks Pilpres - Edy, Dewi Fatmasari; Lestari, Laila Indra; Setyoningtias, Khasdyah Dwi Dewi (Flourishing Journal, 2022)
Abstract: Online groups are a result of the development of the internet which has brought about changes in the pattern of relationships and communication between individuals. Individuals have their own motivations when choosing to join an online group, such as Facebook. Individuals also have the choice to actively contribute or choose to act as lurkers, namely group members who act as non-participants and do not actively contribute to group discussions. The method used is a qualitative approach with an exploratory study design using an open-ended questionnaire and semi-structured interviews. The reasons for individuals choosing to become lurkers in the context of the Presidential Election (Pilpres) in the X Facebook social media group are to avoid conflict, due to busyness so there is no time, due to employment status, due to lack of references and capacity in political commentary, there are discussions that not liked, do not trust the information in the group, are not interested in discussing politics, already feel that there is sufficient information related to politics, there are choices at the beginning, or because they do not trust the threads in the group. Keywords: online group; Facebook; lurker Abstrak: Online group merupakan suatu hasil dari perkembangan internet yang membawa perubahan pola relasi dan komunikasi antarindividu. Individu memiliki motivasi tersendiri ketika memilih untuk bergabung dalam suatu online group, seperti Facebook. Individu pun memiliki pilihan untuk secara aktif memberi kontribusi ataupun memilih untuk berperan sebagai lurker, yaitu anggota grup yang bertindak sebagai non-partisipan dan tidak aktif memberikan kontribusi dalam diskusi grup. Metode yang digunakan adalah pendekatan kualitatif dengan desain studi eksplorasi menggunakan open-ended questionnaire dan wawancara semi-terstruktur. Alasan-alasan individu memilih untuk menjadi lurker dalam konteks Pemilihan Presiden (Pilpres) di grup X media sosial Facebook yaitu untuk menghindari konflik, karena kesibukan sehingga tidak ada waktu, karena status pekerjaan, karena referensi dan kapasitas dalam komentar politik yang kurang, ada pembahasan yang kurang disukai, kurang percaya dengan informasi yang ada dalam grup, tidak tertarik dengan pembahasan politik, sudah merasa tercukupi info terkait politik, sudah ada pilihan diawal, ataupun karena kurang percaya thread di grup. Kata kunci: online group; Facebook; lurker